The reform of federal deposit insurance: the options - M.J.B. HALL (PSL Quarterly Review, 2013)
Discussion of federal deposit insurance reform is currently under way in the United States. The current pressures on deposit insurance funds are thought to have contributed to the present instabilities of the US financial system. The author reviews the issues being raised by the current review. Reform is definitely going to happen, but the nature of such reform is still open to question. Where principles appear to be clear, the practicalities often are not.